THE USE OF “GROW WITH ENGLISH A THEMATIC ENGLISH COURSE FOR ELEMENTARY STUDENT” COURSEBOOK : TEACHER PERCEPTION - Ulfah Rismayanti; Yanuarti Apsari (IKIP Siliwangi, 2021)
Instructional media is an important role for the continuity of the teaching and learning process. There are various types of instructional media that can be used by the teacher. In this opportunity, the researchers conducted the research dealth with the use of coursebook as instructional media in the classroom. This study aims at finding out teacher's perception toward the use of English textbooks in elementary school. This study used descriptive qualitative research design. The respondent of this study is an English teacher of elementary school in West Bandung. The researcher used revealed interview, observation, and document analysis in collecting data. The results of this study that the cover of the book is interesting, the content is easy to understand and the many pictures attract students to learn. Keywords: Teacher Perception, Coursebook